Application of C5 inhibitors in glomerular diseases in 2021 - Alexis Werion; Eric Rondeau (The Korean Society of Nephrology, 2022)
The complement pathway is an essential mechanism in innate immunity, but it is also involved in multiple pathologies. For kidney diseases, strong evidence of a dysregulation in the alternative pathway in atypical hemolytic uremic syndrome (aHUS) led to the use of eculizumab, the first anti-C5 inhibitor available in clinical practice. Intensive fundamental research resulted in the development of subsequent new drugs, such as long-acting C5 inhibitors, oral medications, or antagonists of C5aR, the receptor for C5a. New data in the domain of C5-inhibition in glomerular diseases are still limited and mainly focus on 1) the efficacy of ravulizumab, a long-acting C5 inhibitor in aHUS, and 2) the use of avacopan, a C5aR antagonist, in antineutrophil cytoplasmic antibody vasculitis. Several new studies ongoing or planned for the next few years will evaluate the efficacy of C5 inhibition in secondary thrombotic microangiopathy, C3 glomerulopathy, membranous nephropathy, or immunoglobulin A nephropathy.